The Effect Of Game Science On The Cognitive Development Of Children In Group B PAUD Al-Fatih - Sunandar Azma'ul Hadi (STITNU AL MAHSUNI, 2022)
This study aims to determine whether or not the influence of Game Science on the cognitive development of children in group B PAUD Al-Fatih, Aikdewa Village, Pringgasela District. This type of research is a quantitative research with an experimental approach with One-Group Pretest-Posttest Design, this research takes place in PAUD Al-Fatih, Aikdewa Village, Pringgasela District, 2020/2021 Academic Year. The sample of this study was conducted on 19 children in group B. Methods of data collection using the method of test and observation. The results showed that there was an increase in the cognitive development of early childhood after being given treatment using Game Science by 8.86%. This is also evidenced by the value of Sig. (2-tailed) < 0.05, i.e. 0.000 < 0.05. The research data found that the minimum value was 13 and the maximum value was 19 with the dependent variable normality test, namely cognitive development in the initial test Sig 0.587> 0.05 was declared normal and in the final test Sig 0.771> 0.05 was declared Normal, while the test results homogeneity is known that the significant value is 0.307> 0.05, meaning that the data for the Game Science variable with children's cognitive development has the same variance.